Dynamics of a semiconductor laser with incoherent optical feedback - Houlihan, J.; Huyet, G.; McInerney, J.G. (Optics communications, 2001)
We have experimentally investigated the dynamics of a semiconductor laser with incoherent optical feedback from a single pass external ring cavity. The polarization of the electric field is rotated by 90° before re-injection to avoid interference between the re-injected field and the laser. The dynamics of the laser shows two instabilities: the first is associated with the enhancement of the mode partition noise, while the second is closely connected to the relaxation oscillation and the feedback time.